Flavour chemicals in a sample of non-cigarette tobacco products without explicit flavour names sold in New York City in 2015. Issue 2 (11th April 2017) - Farley, Shannon M; Schroth, Kevin RJ; Grimshaw, Victoria; Luo, Wentai; DeGagne, Julia L; Tierney, Peyton A; Kim, Kilsun; Pankow, James F
Abstract : Background: Youth who experiment with tobacco often start with flavoured products. In New York City (NYC), local law restricts sales of all tobacco products with 'characterising flavours' except for 'tobacco, menthol, mint and wintergreen'. Enforcement is based on packaging: explicit use of a flavour name (eg, 'strawberry') or image depicting a flavour (eg, a fruit) is presumptive evidence that a product is flavoured and therefore prohibited. However, a tobacco product may contain significant levels of added flavour chemicals even when the label does not explicitly use a flavour name. Methods: Sixteen tobacco products were purchased within NYC in 2015 that did not have explicit flavour names, along with three with flavour names. These were analysed for 92 known flavour chemicals plus triacetin by gas chromatography/mass spectrometry. Results: 14 of the 16 products had total determined flavour chemical levels that were higher (>0.3 mg/g) than in previously studied flavour-labelled products and of a chemical profile indicating added flavour chemicals. Conclusions: The results suggest that the tobacco industry has responded to sales restrictions by renaming flavoured products to avoid explicitly identifying them as flavoured. While chemical analysis is the most precise means of identifying flavours in tobacco products, federal tobacco laws pre-empt localities from basing regulations on that approach, limiting enforcement options. If the Food and Drug Administration would mandate that all tobacco products must indicate when flavourings are present above a specific level, local jurisdictions could enforce their sales restrictions. A level of 0.1 mg/g for total added flavour chemicals is suggested here as a relevant reference value for regulating added flavour chemicals in tobacco products.